Effects of water-table depth on seed quality as β-glucan content in waxy and non-waxy naked barley grains - Satoko Yasumoto; Yohei Kawasaki; Hidetoshi Mochizuki; Yuta Shimizu; Satoshi Kawakita (Plant Production Science)
Naked barley (Hordeum vulgare L.) is often planted as a regional specialty crop in the western region of Japan, where there are many hilly and mountainous areas. Water-table depths there are often shallow, due to the inflow of spring melt-water and underground water from the mountains. In this study, the effects of water-table depth on growth and β-glucan content in naked barley were studied by using a lysimeter. The new, waxy-type, naked barley cultivar ‘Fukumifiber’, with high β-glucan content, showed that β-glucan content per grain with same ripeness were decreased by shallower water-table depth, while in the non-waxy cultivar ‘Ichibanboshi’, the effect to β-glucan content per grain was not significant. During ripening, the β-glucan content in both waxy and non-waxy cultivars increased sharply from the 20th to the 30th days after anthesis. In waxy-type cultivar ‘Fukumifiber’, β-glucan further accumulated from the 30th to the 50th days after anthesis, but the accumulation was suppressed as the water-table depth shallowed. While in non-waxy type cultivar ‘Ichibanboshi’, there was no significant increase from the 30th to the 50th days after anthesis and there were no significant differences due to the water-table depth. These results suggest that good drainage may be particularly important before from the 20th to the 30th days after anthesis for all cultivars. Furthermore, for some cultivars similar measures until the 50th day after anthesis may also be important. And even under shallow water-table depth condition, the difference between cultivars that have high β-glucan content or low content was maintained.